2005
DOI: 10.1021/ic050880o
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interaction of Platinum(II) Complexes with 1,10-Phenanthroline and Extended Phenanthrolines

Abstract: The interaction with DNA of the platinum(II) square planar complexes [Pt(N-N)(py)(2)](2+) (N-N = 1,10-phenanthroline (phen), dipyrido[3,2-d:2',3'-f]quinoxaline (dpq), dipyrido[3,2-a:2',3'-c]phenazine (dppz), benzodipyrido[b:3,2-h:2'3'-f]phenazine (bdppz)) has been investigated by means of absorption, circular and linear dichroism spectroscopy, DNA melting, and viscosity. In the presence of excess [DNA] all the complexes intercalate to the double helix. For those with the most extended phenanthrolines the bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 44 publications
5
58
0
1
Order By: Relevance
“…For 7, an even larger DT m value (27.0 ± 0.6 • C) was determined and, like EtBr, its strong propensity to intercalate DNA has been demonstrated by means of other spectroscopic methods. 2 Interestingly, none of the four boronic acid complexes exhibited large DT m values, with the largest DT m (2.6 ± 0.6 • C) being observed for 4. It is unlikely that the small DT m values are the result of steric hindrance between the complexes and DNA because the boronic acid groups, particularly those found in the 4-pyridineboronic acid derivatives 5 and 6, are located remotely from the intercalating diimine ligands.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For 7, an even larger DT m value (27.0 ± 0.6 • C) was determined and, like EtBr, its strong propensity to intercalate DNA has been demonstrated by means of other spectroscopic methods. 2 Interestingly, none of the four boronic acid complexes exhibited large DT m values, with the largest DT m (2.6 ± 0.6 • C) being observed for 4. It is unlikely that the small DT m values are the result of steric hindrance between the complexes and DNA because the boronic acid groups, particularly those found in the 4-pyridineboronic acid derivatives 5 and 6, are located remotely from the intercalating diimine ligands.…”
Section: Introductionmentioning
confidence: 90%
“…The deboronated species 7 was used as a model compound as its avid DNA-binding has been investigated recently. 2 The wellknown intercalator ethidium bromide (EtBr) was used as the control. The results of the DNA thermal denaturation experiments are presented in Table 1, and a typical DNA melting plot is presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Among these gold(III) and platinum(II) containing compounds, Au(III) and Pt(II) complexes of 1,10-phenanthroline (phen) were reported to be cytotoxic to several tumour cells. Messori and co-workers (2002) demonstrated significant cytotoxic activity of Au(III) complexes with 1,10-phenanthroline (phen) against human ovarian cancer cells (A2780); on the other hand, Cusumano and co-workers (2006) showed that Pt(II) complexes of 1,10-phenanthroline (phen) have DNA binding properties 11,13,14 . It is also well known that 1,10-phenanthroline (phen) is the parent of an important class of chelating agents and has structural features such as a rigid planar, hydrophobic, and its electron-poor heteroaromatic system whose nitrogen atoms are beautifully placed to act cooperatively in cation binding.…”
Section: Research Articlementioning
confidence: 99%
“…The Au(III) and Pt(II) complexes of 1,10-phenanthroline (phen), ([Au(phen)Cl 2 ]Cl and Pt(phen)Cl 2 were synthesized by using literature methods 13,14 . The compounds gave satisfactory elemental analysis.…”
Section: Chemistrymentioning
confidence: 99%
“…32 Mixtures of CT-DNA and complexes ([base pairs]/[complex] = 10) were prepared in phosphate-buffered saline solution (pH 7.4) and their thermal denaturation monitored spectrophotometrically over the temperature range 37-100 • C. Data were fitted to sigmoidal plots with the maxima of the first derivatives occurring at T m c . The data acquired for CT-DNA in the absence of metal complex (T m…”
Section: Thermal Denaturation Experimentsmentioning
confidence: 99%